KSPI, KTPPU, TLRHP DAN OPINI BPK ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Arianto, Handoko; Heriyanto, Meyzi; Karneli, Okta (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
KSPI, KTPPU, TLRHP and Opinion of BPK on Local Government Financial Report. The objectives of this research are to identify and analyze the influence of Internal Control System (KSPI), Findings of Disobedience to Legislation (KTPPU) and Follow-up Recommendation of Examination Result (TLRHP) to BPK's opinion. Population and sample in this research are Province LKPD Entity and 12 Regency / City in Riau Province which become object of Inspection of Financial Statement (LK) and Inspection with Specific Purposes (PDTT) by BPK Representative of Riau Province 2010 - 2016. Analytical tool used is multiple linear regression. The results showed that partially independent variables consisting of KSPI findings, KTPPU and TLRHP findings have a significant influence on BPK's opinion on provincial LKPD and 12 districts / cities in Riau Province in 2010-2016. While simultaneously, the influence of the three independent variables on the dependent variable is equal to 74.7%. Thus, there are still 25.3% more other factors that influence the CPC Opinion outside the regression model.